2021
DOI: 10.11646/phytotaxa.501.1.1
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>The vascular plant diversity of Dzungarian Gobi in western Mongolia, with an annotated checklist</strong></p>

Abstract: The Dzungarian Gobi (DzG), one of 16 phytogeographical regions in the country, is located in the southwestern part of Khovd province in western Mongolia. It comprises some of Mongolia’s largest reserves, namely the Great Gobi B Strictly Protected Area and the National Park Bulgan gol-Ikh Ongog. We conducted a comprehensive survey of the area’s floristic diversity between 2009 and 2019 by collecting vascular plants from different vegetation types in various seasons. In addition, we critically checked relevant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…V.V.Botschantz, and Saussurea saichanensis Komarov ex Lipsch, and concluded that the species are in no immediate danger [15,16]. However, because many endemic plants are restricted to type specimen localities or have limited geographical ranges [14,47], special attention should be given to the species' evaluation and protection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…V.V.Botschantz, and Saussurea saichanensis Komarov ex Lipsch, and concluded that the species are in no immediate danger [15,16]. However, because many endemic plants are restricted to type specimen localities or have limited geographical ranges [14,47], special attention should be given to the species' evaluation and protection.…”
Section: Discussionmentioning
confidence: 99%
“…Regional distribution (RD) in Mongolia was based on Grubov [18], Gubanov [13], Urgamal et al [2], and Baasanmunkh et al [47]: 1-Khuvsgul, 2-Khentei, 3-Khangai, 4-Mongolian Dauria, 5-Foothills of Great Khyangan, 6-Khovd, 7-Mongolian Altai, 8-Middle Khalkh, 9-East Mongolia, 10-Depression of Great Lakes, 11-Valley of Lakes, 12-East Gobi, 13-Gobi Altai, 14-Dzungarian Gobi, 15-Transaltai Gobi, and 16-Alashan Gobi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dactylorhiza Sw. Dactylorhiza is the most difficult genus among orchids to identify because of morphological plasticity, ongoing evolution, and wide hybridization; therefore, the status of accepted species changes continually [37,42]. Currently, six taxa have been reported in Mongolia [23][24][25]43], but the number of species may vary depending on the author. One of the most taxonomically problematic groups is 'salina-aggregate', which is represented in the current overview by two species, viz.…”
Section: Taxonomic Notes On Selected Generamentioning
confidence: 99%